Public Works Programmes and Cooperation for the Common Good: Evidence from Malawi - Stefan Beierl; Marina Dodlova (The European Journal of Development Research, 2022)
This paper investigates the relationship between Malawi's largest and oldest public works programme (PWP) and social cohesion, specifically within-community cooperation for the common good. Using both primary and secondary data, we show that public works are associated with higher coordination activities and higher voluntary (unpaid) contributions to public goods, along both vertical ties (between community members and local leaders) and horizontal ties (among community members). Especially for school-building activities, voluntary inputs in the form of labour and other in-kind contributions are higher in the presence of the PWP. Our results contribute to a better understanding of the link between social protection programmes with community-driven features and social cohesion.
Keywords: 330; Public works; Cash-for-work; Social protection; Cooperation for the common good; Coordination; Community meeting; Voluntary contributions